Decreased Proliferation of Adult Hippocampal Stem Cells During Cocaine Withdrawal: Possible Role of the Cell Fate Regulator FADD - García-Fuster, M Julia (Nature Publishing Group, 2011)
The current study uses an extended access rat model of cocaine self-administration (5-h session per day, 14 days), which elicits several features manifested during the transition to human addiction, to study the neural adaptations associated with cocaine withdrawal. Given that the hippocampus is thought to have an important role in maintaining addictive behavior and appears to be especially relevant to mechanisms associated with withdrawal, this study attempted to understand how extended access to cocaine impacts the hippocampus at the cellular and molecular levels, and how these alterations change over the course of withdrawal (1, 14, and 28 days). Therefore, at the cellular level, we examined the effects of cocaine withdrawal on cell proliferation (Ki-67+ and NeuroD+ cells) in the DG. At the molecular level, we employed a ‘discovery' approach with gene expression profiling in the DG to uncover novel molecules possibly implicated in the neural adaptations that take place during cocaine withdrawal. Our results suggest that decreased hippocampal cell proliferation might participate in the adaptations associated with drug removal and identifies 14 days as a critical time-point of cocaine withdrawal. At the 14-day time-point, gene expression profiling of the DG revealed the dysregulation of several genes associated with cell fate regulation, highlighting two new neurobiological correlates (Ascl-1 and Dnmt3b) that accompany cessation of drug exposure. Moreover, the results point to Fas-Associated protein with Death Domain (FADD), a molecular marker previously associated with the propensity to substance abuse and cocaine sensitization, as a key cell fate regulator during cocaine withdrawal. Identifying molecules that may have a role in the restructuring of the hippocampus following substance abuse provides a better understanding of the adaptations associated with cocaine withdrawal and identifies novel targets for therapeutic intervention.